AB1162 Looking for minimum standards in care for children with localized scleroderma-result of the consensus meeting in hamburg germany on the 11th of december 2011. Part I. diagnosis and assessment of the disease. (23rd January 2014) - Foeldvari, I.; Constantin, T.; Höger, P.; Nemcova, D.; Pain, C.; Torok, K.; Weibel, L.; Clements, P.
Abstract : Background: Juvenile localised scleroderma (jlSc) is an orphan disease. There are currently no guidelines regarding diagnosis, follow up and treatment. Objectives: In the frame of the PRES scleroderma working group this consensus meeting was set up to gain consensus regarding these issues. Methods: Members of the PRES scleroderma working group were invited to participate. Two pediatric dermatologists were invited. P. Clements was invited to moderate the meeting. A nominal group technique was used. 75% consensus was defined as agreement. Results: The following agreements were reached: Diagnosis is based on clinical grounds by a rheumatologist or dermatologist, preferably pediatric, with a biopsy as a confirmatory measure if it is unclear based on clinical findings. If a biopsy is needed, a punch biopsy is appropriate. In the case of deep involvement, a deep biopsy is needed. Since progression to systemic sclerosis is unlikely, an evaluation for internal organ involvement, such as HRCT and echocardiogram, is unnecessary There are no laboratory studies needed to confirm the diagnosis. The group agrees there is no clear evidence for a pathogenic role of Borrelia, therefore we do not recommend investigation for Borrelia infection. In patients with sclerodermatous skin changes of the head (face and/or scalp) the following are suggested: MRI of the brain, preferably with contrast. In the absence of clear evidence, the group suggested to screen every 6 months for uveitis with slit lamp examination for the first 4 years of the disease. Dental assessment is strongly suggested, especially if the lesion crosses the maxilla and mandible. Temporomandibular joint assessment by a pediatric rheumatologist every 6 months is suggested. In the absence of clear evidence, the group suggested to screen every 12 months for uveitis with slit lamp examination for the first 4 years of the disease, if the lesion does not involves the face. All patients besides superficial circumscribed localised scleroderma (plaque morphea), especially those with linear disease, are suggested to be seen at baseline and every 12 months by both a pediatric rheumatologist and pediatric dermatologist, ideally in combined clinic. The group suggested using the LoSCAT (Localized Scleroderma Cutaneous Assessment Tool) to assess cutaneous activity and damage measures. There is a need to assess the quality of life of jLS patients. Conclusions: Although there are no solid guidelines currently present as the "standard of care" for jLs, these suggestions are part of routine care for most physicians specializing in the care of pediatric localized scleroderma and are non-invasive measures. Disclosure of Interest: None Declared